Electron–phonon interaction in Gd1- xCaxBaSrCu3O7-8 superconductors - Chong, T.V.; Kambe, S.; Kawaji, H.; Atake, T.; Ishii, O. (Elsevier, 2012)
Polycrystalline Gd1−xCaxBaSrCu3O7−ı samples (0 ≤ x ≤ 0.1) were prepared via solid-state reaction. The superconducting critical temperature Tc and lattice parameter decrease with doping content. Temperature dependence of the specific heat of all samples was measured with the thermal relaxation technique using a Physical Property Measurement System from about 2 K to 150 K. The calculated Debye temperature D at 10 K is found to be inversely proportional to Tc. Subsequently, the electron–phonon coupling constant was estimated based on standard BCS theory (BCS) in the weak coupling limit and twodimensional Van Hove scenario (VH). The calculated values of VH in this study (around 0.04) are close to the experimental data as reported by other researchers on Bi-based and YBCO samples. Hence, the twodimensional Van Hove scenario seems to be a viable candidate for the mechanism of superconductivity if electron–phonon coupling plays a role in superconductivity of these materials.